PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA TRANSAKSI DENGAN SISTEM PEMBAYARAN GO-PAY - Lusi Septiyati; Siti Nurbaiti (Jurnal Hukum Adigama, 2019)
The development of technology, information and communication affects Indonesian people in making payment, one among which is using Go-Pay payment system. However, the system does not always work well because it is still prone of problems such as loss of balance during Go-Pay transaction. Legal protection for consumers using Go-Pay payment system is the problem to be discussed in the thesis. The research uses descriptive normative legal method, making use of secondary and primary data as the supporting data with legal approach. The research findings illustrate that consumers in Go-Pay payment system have no legal protection because GO-JEK does not provide compensation as provided for in Article 4 paragraph (8) of the Consumer Protection Law, Article 7 paragraph (6) of the Consumer Protection Law, Article 19 of the Consumer Protection Law, Article 43 of Bank Indonesia Regulation Number 14, item (3) of Go-Pay Terms and Conditions. It is suggested that GO-JEK should provide legal protection to its consumers by complying with regulations and carrying out its obligations to provide compensation.